Sintered foil slurry and preparation method thereof

By using spherical aluminum alloy powder, silicon phosphide, black phosphorus and silicon carbide in the sintered foil slurry, and using high-speed ball milling and other technical means, these raw materials are evenly dispersed, solving the problem that existing sintered foil slurry is difficult to take into account capacity, heat dissipation, stability and high efficiency, and improving the high specific capacity, good heat dissipation, stability and mechanical properties of sintered foils are achieved.

CN119361325BActive Publication Date: 2025-04-18HENAN WEINA ELECTRONIC MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411925895.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-18
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The existing sintered foil slurry is difficult to take into account capacity, heat dissipation, stability and high efficiency, resulting in insufficient performance of aluminum electrolytic capacitors.

Method used

Through the combination of specific raw materials and preparation methods, a slurry for sintered foil, including spherical aluminum alloy powder, silicon phosphide, black phosphorus and silicon carbide, are prepared, and high-speed ball milling and other technical means are used to uniformly disperse these raw materials, thereby improving the specific surface area and comprehensive performance of the sintered foil.

Benefits of technology

The high specific capacity, good heat dissipation, stability and mechanical properties of the sintered foil are achieved, and the overall performance of the aluminum electrolytic capacitor is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of sintered foil, specifically to a sintered foil slurry and a preparation method thereof, the method comprising: mixing spherical aluminum alloy powder, polyvinylidene fluoride and dimethylformamide, using a first high-speed ball milling to evenly disperse the aluminum alloy powder in dimethylformamide to form an aluminum alloy powder slurry; mixing silicon phosphide, black phosphorus, a surfactant and dihydrogen levoglucose ketone, using a cell crusher to evenly disperse silicon phosphide and black phosphorus in dihydrogen levoglucose ketone to obtain a uniformly distributed silicon phosphide and black phosphorus dihydrogen levoglucose ketone dispersion; adding the silicon phosphide and black phosphorus dihydrogen levoglucose ketone dispersion to the aluminum alloy powder slurry, and performing a second high-speed ball milling to evenly disperse silicon phosphide and black phosphorus in the slurry. The present application makes the slurry for sintered foil evenly dispersed by matching specific raw materials and preparation methods, thereby increasing the specific surface area of ​​the sintered foil and enhancing the capacitance, heat dissipation and stability of the capacitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of sintered foils, and in particular to a sintered foil slurry and a preparation method thereof. Background Art

[0002] Capacitors are electronic components composed of two adjacent and insulated conductors used to store electrical energy. Capacitors can store electrical energy efficiently and release it quickly when needed. They have significant advantages in circuits that require fast charging and discharging. They also have the characteristics of high power density, long service life, and a wide operating range. As an important electronic component, aluminum electrolytic capacitors are widely used in home appliances such as mobile phones and televisions, and can be used as power sources for hybrid vehicles, aerospace and other fields.

[0003] Capacitor sintered foil is a high-performance material formed by firmly combining aluminum powder or other metal powder with an aluminum foil substrate through a specific sintering process. Sintered foil is usually used as anode foil for aluminum electrolytic capacitors and has excellent properties such as high specific capacitance and high energy storage density.

[0004] Sintered foil slurry is a key material for preparing sintered foil, which affects the comprehensive performance of aluminum electrolytic capacitors. With the continuous development of the electronics industry, the performance requirements for aluminum electrolytic capacitors are getting higher and higher. Sintered foil made of general sintered foil slurry is difficult to take into account the performance of capacity, heat dissipation, stability, and high efficiency. Summary of the invention

[0005] The present application aims to overcome at least one of the defects of the prior art and provide a sintered foil slurry and a preparation method thereof. By matching specific raw materials and preparation methods, the sintered foil slurry is evenly dispersed, the specific surface area of ​​the sintered foil is increased, and the capacitance, heat dissipation and stability of the capacitor are enhanced.

[0006] In a first aspect, the present application provides a method for preparing a sintered foil slurry, which is achieved by the following technical solutions:

[0007] A method for preparing a sintered foil slurry comprises the following steps:

[0008] (1) 70-85 parts of spherical aluminum alloy powder, 5-10 parts of polyvinylidene fluoride and 80-100 parts of dimethylformamide are mixed according to weight parts, and the aluminum alloy powder is uniformly dispersed in the dimethylformamide by a first high-speed ball mill to form a uniform aluminum alloy powder slurry;

[0009] (2) Mixing 2-4 parts of silicon phosphide, 1-2 parts of black phosphorus, 2-3 parts of a surfactant and 10-15 parts of dihydro-L-glucose ketone according to weight parts, and uniformly dispersing the silicon phosphide and black phosphorus in the dihydro-L-glucose ketone using a cell crusher to obtain a dihydro-L-glucose ketone dispersion in which silicon phosphide and black phosphorus are uniformly distributed;

[0010] (3) adding the silicon phosphide and black phosphorus dihydrogen levorotatory glucosone dispersion liquid described in step (2) to the aluminum alloy powder slurry described in step (1), and performing a second high-speed ball milling to evenly disperse the silicon phosphide and black phosphorus in the slurry to obtain a sintered foil slurry;

[0011] The spherical aluminum alloy powder in step (1) comprises the following raw materials in parts by weight: 60-80 parts of aluminum powder, 3-5 parts of silicon carbide, 10-15 parts of nano zinc powder, 2-3 parts of magnesium powder, and 2-3 parts of titanium powder;

[0012] The surface of the silicon carbide is plated with a tin-lead alloy layer.

[0013] According to a method for preparing a sintered foil slurry according to an embodiment of the present application, there are at least the following beneficial effects:

[0014] The spherical aluminum alloy powder of the present application has a large specific surface area, which helps to achieve a micro-melting state between aluminum alloy powders and between aluminum alloy powders and aluminum foil during sintering, so that they can be effectively combined to form a porous spherical stacking structure, thereby improving the specific capacity of the aluminum alloy powder sintered anode foil.

[0015] The silicon phosphide of the present application has excellent high-temperature stability, high power characteristics, high thermal conductivity and corrosion resistance. Adding it to the slurry can improve the heat dissipation, corrosion resistance and stability of the sintered foil. At the same time, it has a high specific surface area. Adding silicon phosphide during the sintering process is beneficial to the contact between aluminum alloy powders, thereby improving the sintering performance.

[0016] The black phosphorus of the present application has an ultra-high specific surface area as a two-dimensional material. Adding black phosphorus during the sintering process is beneficial to the contact between aluminum alloy powders, thereby improving the sintering performance. At the same time, black phosphorus has a high specific capacity. Adding an appropriate amount of black phosphorus can increase the specific capacity of the sintered foil. In addition, black phosphorus has high strength and conductivity, which can further improve the mechanical properties and conductivity of the sintered foil.

[0017] The addition of silicon carbide particles in the present application can fill the microscopic defects and voids in the aluminum alloy, thereby enhancing the strength and hardness of the alloy and improving the overall physical stability of the capacitor. Silicon carbide has a very high thermal conductivity. Adding it to the aluminum alloy can significantly improve the thermal conductivity of the material, which helps the capacitor to dissipate heat more effectively and maintain its stable operation. Adding silicon carbide to the aluminum alloy can also improve its corrosion resistance, reduce oxidation and corrosion of the aluminum alloy, and extend the service life of the capacitor.

[0018] The surface of the silicon carbide of the present application is coated with a tin-lead alloy layer, which can improve the affinity of silicon carbide, improve the wettability of the molten pool to silicon carbide, and help improve the distribution uniformity of silicon carbide particles. The tin element in the tin-lead alloy can reduce the surface tension of the liquid phase, making it easier for the liquid phase generated during the sintering process to fill the pores. In addition, during the sintering process, the liquid phase tin can spread on the surface of the aluminum powder, reduce the oxidation rate of the aluminum powder, and improve the sintering performance.

[0019] The addition of surfactant, dimethylformamide and dihydrolevoglucose in the preparation method of the present application can improve the surface activity of the powder, reduce the agglomeration of the powder, and make the particle size distribution more uniform, thereby improving the comprehensive performance of the sintered foil. The effect of the combination of dimethylformamide and dihydrolevoglucose is better than the effect of using either one alone, and can maintain the dispersed state of the particles and improve the stabilizing effect on the slurry powder for sintered foil.

[0020] Zinc in this application is the main liquid phase forming element, which produces an instantaneous liquid phase during the sintering process to achieve sintering densification; the magnesium element has a fast diffusion rate, which can quickly break down the small amount of oxide film that may exist on the surface of the aluminum powder, forming a semi-continuous MgO and MgAl2O4 oxide layer at the grain boundary, and at the same time forming a MgZn2 reinforcing phase with the Zn element to improve the strength of the aluminum alloy material.

[0021] According to some embodiments of the present application, the method for preparing the spherical aluminum alloy powder includes the following steps: mixing the raw materials for preparing the spherical aluminum alloy powder according to weight parts, subjecting the mixture to electromagnetic induction heating, and gradually melting the mixture into liquid metal; subsequently, under the action of an inert gas jet, the liquid metal is blown into small droplets in the micrometer range and cooled into spherical aluminum alloy powder.

[0022] During the cooling process, due to the effect of surface tension, the droplets tend to be spherical, and the solidified powder particles are spherical with a large specific surface area, thereby increasing the specific capacity of the aluminum alloy powder sintered anode foil.

[0023] Furthermore, the heating temperature is 700-800°C.

[0024] Furthermore, the average particle size of the spherical aluminum alloy powder is 2-3 μm.

[0025] Furthermore, the inert gas is selected from one of nitrogen, helium, neon, and argon, for example, the protective gas is nitrogen. Nitrogen is widely available and has a low production cost. It can form an oxygen-free environment to prevent oxidation damage to metals such as aluminum and titanium and reduce the generation of impurities. Rare gases such as helium, neon, and argon are stable in nature and are not easily involved in chemical reactions, which can reduce the generation of oxide impurities.

[0026] Furthermore, the pressure of the inert gas injection is 100-300 kPa.

[0027] Furthermore, the inert gas jetting speed is 600-800 m / s.

[0028] According to some embodiments of the present application, the average particle size of the silicon carbide is 1-2 μm. This particle size can better balance the comprehensive properties of the aluminum alloy material, such as strength, thermal conductivity, corrosion resistance, and powder fluidity, and is more conducive to improving the comprehensive properties of the aluminum alloy material.

[0029] According to some embodiments of the present application, the surfactant in step (2) is selected from one of ethanol, isopropanol, glycerol, and citric acid.

[0030] According to some embodiments of the present application, the rotation speed of the first high-speed ball milling in step (1) is 300-600 r / min; further, 300-550 r / min.

[0031] Furthermore, the time of the first high-speed ball milling in step (1) is 5-10 hours; further, 6-8 hours.

[0032] According to some embodiments of the present application, the rotation speed of the second high-speed ball milling in step (3) is 300-600 r / min; further, 300-550 r / min.

[0033] Furthermore, the time of the second high-speed ball milling in step (3) is 5-10 hours; further, 6-8 hours.

[0034] In a second aspect, an embodiment of the present application provides a sintered foil slurry produced by the above-mentioned method for preparing a sintered foil slurry.

[0035] The slurry for sintering foil according to the embodiment of the present application has at least the following beneficial effects:

[0036] The sintered foil slurry of the present application is not easy to agglomerate, and the particles are evenly distributed, which can improve the density and heat dissipation, corrosion resistance, specific capacity and other properties of the sintered foil.

[0037] In a third aspect, an embodiment of the present application provides a use of the above-mentioned sintered foil slurry in the production of sintered foil.

[0038] In a fourth aspect, the present application provides an application of the above sintered foil slurry in making capacitors. The capacitors prepared using the sintered foil slurry of the present application have high capacitance, good heat dissipation, corrosion resistance, and a more solid structure with good stability in use. DETAILED DESCRIPTION

[0039] To make the purpose, technical solution and advantages of the present application clearer, the following will be further described in detail in conjunction with specific embodiments. The embodiments described here are only part of the embodiments of the present application and cannot be understood as limiting the scope of protection of the present application.

[0040] Example 1

[0041] Preparation of slurry for sintering foil:

[0042] (1) 78 parts of spherical aluminum alloy powder, 8 parts of polyvinylidene fluoride and 90 parts of dimethylformamide were mixed according to weight parts, and the aluminum alloy powder was uniformly dispersed in dimethylformamide by a first high-speed ball mill at a speed of 420 r / min for 7 hours to form a uniform aluminum alloy powder slurry;

[0043] (2) Mix 3 parts of silicon phosphide, 1.5 parts of black phosphorus, 2.5 parts of isopropanol and 12 parts of dihydro-L-glucose ketone according to weight parts, and use a cell crusher to evenly disperse the silicon phosphide and black phosphorus in the dihydro-L-glucose ketone to obtain a dihydro-L-glucose ketone dispersion in which silicon phosphide and black phosphorus are evenly distributed;

[0044] (3) adding the silicon phosphide and black phosphorus dihydrogen levorotatory glucosone dispersion liquid described in step (2) to the aluminum alloy powder slurry described in step (1), and performing a second high-speed ball milling at a rotation speed of 420 r / min for 7 h to uniformly disperse the silicon phosphide and black phosphorus in the slurry to obtain a sintered foil slurry;

[0045] The preparation method of the spherical aluminum alloy powder is as follows: 70 parts of aluminum powder, 4 parts of silicon carbide, 13 parts of nano zinc powder, 2.5 parts of magnesium powder, and 2.5 parts of titanium powder are mixed according to weight parts, and the temperature is maintained at 750°C for electromagnetic induction heating to gradually melt into a metal liquid; then, under the action of nitrogen injection at a pressure of 200 kPa and a speed of 700 m / s, the metal liquid is blown into micron-sized droplets, and cooled into a spherical aluminum alloy powder with an average particle size of 2-3 μm;

[0046] The surface of silicon carbide is plated with a tin-lead alloy layer; the average particle size of silicon carbide is 1-2 μm.

[0047] Example 2

[0048] Preparation of slurry for sintering foil:

[0049] (1) 70 parts of spherical aluminum alloy powder, 10 parts of polyvinylidene fluoride and 80 parts of dimethylformamide were mixed according to weight parts, and the aluminum alloy powder was uniformly dispersed in dimethylformamide by a first high-speed ball mill at a speed of 550 r / min for 6 hours to form a uniform aluminum alloy powder slurry;

[0050] (2) Mix 4 parts of silicon phosphide, 1 part of black phosphorus, 3 parts of glycerol and 10 parts of dihydro-L-glucose ketone according to weight parts, and use a cell crusher to evenly disperse the silicon phosphide and black phosphorus in the dihydro-L-glucose ketone to obtain a dihydro-L-glucose ketone dispersion in which silicon phosphide and black phosphorus are evenly distributed;

[0051] (3) adding the silicon phosphide and black phosphorus dihydrogen levorotatory glucosone dispersion liquid described in step (2) to the aluminum alloy powder slurry described in step (1), and performing a second high-speed ball milling at a rotation speed of 600 r / min for 5 h to uniformly disperse the silicon phosphide and black phosphorus in the slurry to obtain a sintered foil slurry;

[0052] The preparation method of the spherical aluminum alloy powder is as follows: 80 parts of aluminum powder, 3 parts of silicon carbide, 15 parts of nano zinc powder, 2 parts of magnesium powder and 3 parts of titanium powder are mixed according to weight, and the temperature is maintained at 700°C for electromagnetic induction heating to gradually melt into a metal liquid; then, under the action of a helium jet at a pressure of 300 kPa and a speed of 600 m / s, the metal liquid is blown into micron-sized droplets, and cooled into a spherical aluminum alloy powder with an average particle size of 2-3 μm;

[0053] The surface of silicon carbide is plated with a tin-lead alloy layer; the average particle size of silicon carbide is 1-2 μm.

[0054] Example 3

[0055] Preparation of slurry for sintering foil:

[0056] (1) 85 parts of spherical aluminum alloy powder, 5 parts of polyvinylidene fluoride and 100 parts of dimethylformamide were mixed according to weight parts, and the aluminum alloy powder was uniformly dispersed in dimethylformamide by a first high-speed ball mill at a speed of 300 r / min for 10 hours to form a uniform aluminum alloy powder slurry;

[0057] (2) Mix 2 parts of silicon phosphide, 2 parts of black phosphorus, 2 parts of citric acid and 15 parts of dihydro-L-glucose ketone according to weight parts, and use a cell crusher to evenly disperse the silicon phosphide and black phosphorus in the dihydro-L-glucose ketone to obtain a dihydro-L-glucose ketone dispersion in which silicon phosphide and black phosphorus are evenly distributed;

[0058] (3) adding the silicon phosphide and black phosphorus dihydrogen levorotatory glucosone dispersion liquid described in step (2) to the aluminum alloy powder slurry described in step (1), and performing a second high-speed ball milling at a rotation speed of 300 r / min for 8 h to uniformly disperse the silicon phosphide and black phosphorus in the slurry to obtain a sintered foil slurry;

[0059] The preparation method of the spherical aluminum alloy powder is as follows: 60 parts of aluminum powder, 5 parts of silicon carbide, 10 parts of nano zinc powder, 3 parts of magnesium powder and 2 parts of titanium powder are mixed according to weight parts, and the temperature is maintained at 800°C for electromagnetic induction heating to gradually melt into a metal liquid; then, under the action of a neon gas jet at a pressure of 100 kPa and a speed of 800 m / s, the metal liquid is blown into micron-sized droplets, and cooled into a spherical aluminum alloy powder with an average particle size of 2-3 μm;

[0060] The surface of silicon carbide is plated with a tin-lead alloy layer; the average particle size of silicon carbide is 1-2 μm.

[0061] Example 4

[0062] Preparation of slurry for sintering foil:

[0063] (1) 80 parts of spherical aluminum alloy powder, 7 parts of polyvinylidene fluoride and 90 parts of dimethylformamide were mixed according to weight parts, and the aluminum alloy powder was uniformly dispersed in dimethylformamide by a first high-speed ball mill at a speed of 450 r / min for 9 hours to form a uniform aluminum alloy powder slurry;

[0064] (2) Mix 3 parts of silicon phosphide, 1 part of black phosphorus, 3 parts of ethanol and 14 parts of dihydro-L-glucose ketone according to weight parts, and use a cell crusher to evenly disperse the silicon phosphide and black phosphorus in the dihydro-L-glucose ketone to obtain a dihydro-L-glucose ketone dispersion in which silicon phosphide and black phosphorus are evenly distributed;

[0065] (3) adding the silicon phosphide and black phosphorus dihydrogen levorotatory glucosone dispersion liquid described in step (2) to the aluminum alloy powder slurry described in step (1), and performing a second high-speed ball milling at a rotation speed of 500 r / min for 7 h to uniformly disperse the silicon phosphide and black phosphorus in the slurry to obtain a sintered foil slurry;

[0066] The preparation method of the spherical aluminum alloy powder is as follows: 70 parts of aluminum powder, 4 parts of silicon carbide, 12 parts of nano zinc powder, 2 parts of magnesium powder, and 3 parts of titanium powder are mixed according to weight, and the temperature is maintained at 750°C for electromagnetic induction heating to gradually melt into a metal liquid; then, under the action of an argon gas jet at a pressure of 200 kPa and a speed of 700 m / s, the metal liquid is blown into micron-sized droplets, and cooled into a spherical aluminum alloy powder with an average particle size of 2-3 μm;

[0067] The surface of silicon carbide is plated with a tin-lead alloy layer; the average particle size of silicon carbide is 1-2 μm.

[0068] Comparative Example 1

[0069] Preparation of slurry for sintering foil:

[0070] (1) 78 parts of spherical aluminum alloy powder, 8 parts of polyvinylidene fluoride and 90 parts of dimethylformamide were mixed according to weight parts, and the aluminum alloy powder was uniformly dispersed in dimethylformamide by a first high-speed ball mill at a speed of 420 r / min for 7 hours to form a uniform aluminum alloy powder slurry;

[0071] (2) Mixing 1.5 parts of black phosphorus, 2.5 parts of isopropanol and 12 parts of dihydro-L-glucose ketone according to weight parts, and using a cell crusher to evenly disperse the black phosphorus in the dihydro-L-glucose ketone to obtain a uniformly distributed black phosphorus-L-glucose ketone dispersion;

[0072] (3) adding the dihydrogen levulose ketone dispersion of black phosphorus described in step (2) to the aluminum alloy powder slurry described in step (1), and performing a second high-speed ball milling at a rotation speed of 420 r / min for 7 h to uniformly disperse the black phosphorus in the slurry to obtain a sintered foil slurry;

[0073] The preparation method of the spherical aluminum alloy powder is as follows: 70 parts of aluminum powder, 4 parts of silicon carbide, 13 parts of nano zinc powder, 2.5 parts of magnesium powder, and 2.5 parts of titanium powder are mixed according to weight parts, and the temperature is maintained at 750°C for electromagnetic induction heating to gradually melt into a metal liquid; then, under the action of nitrogen injection at a pressure of 200 kPa and a speed of 700 m / s, the metal liquid is blown into micron-sized droplets, and cooled into a spherical aluminum alloy powder with an average particle size of 2-3 μm;

[0074] The surface of silicon carbide is plated with a tin-lead alloy layer; the average particle size of silicon carbide is 1-2 μm.

[0075] Comparative Example 2

[0076] Preparation of slurry for sintering foil:

[0077] (1) 78 parts of spherical aluminum alloy powder, 8 parts of polyvinylidene fluoride and 90 parts of dimethylformamide were mixed according to weight parts, and the aluminum alloy powder was uniformly dispersed in dimethylformamide by a first high-speed ball mill at a speed of 420 r / min for 7 hours to form a uniform aluminum alloy powder slurry;

[0078] (2) Mix 3 parts of silicon phosphide, 2.5 parts of isopropanol and 12 parts of dihydro-levulinic acid ketone according to weight parts, and use a cell crusher to evenly disperse the silicon phosphide in the dihydro-levulinic acid ketone to obtain a uniformly distributed silicon phosphide dihydro-levulinic acid ketone dispersion;

[0079] (3) adding the silicon phosphide dihydrogen levorotatory glucosone dispersion described in step (2) to the aluminum alloy powder slurry described in step (1), and performing a second high-speed ball milling at a rotation speed of 420 r / min for 7 h to uniformly disperse the silicon phosphide in the slurry to obtain a sintered foil slurry;

[0080] The preparation method of the spherical aluminum alloy powder is as follows: 70 parts of aluminum powder, 4 parts of silicon carbide, 13 parts of nano zinc powder, 2.5 parts of magnesium powder, and 2.5 parts of titanium powder are mixed according to weight parts, and the temperature is maintained at 750°C for electromagnetic induction heating to gradually melt into a metal liquid; then, under the action of nitrogen injection at a pressure of 200 kPa and a speed of 700 m / s, the metal liquid is blown into micron-sized droplets, and cooled into a spherical aluminum alloy powder with an average particle size of 2-3 μm;

[0081] The surface of silicon carbide is plated with a tin-lead alloy layer; the average particle size of silicon carbide is 1-2 μm.

[0082] Comparative Example 3

[0083] Preparation of slurry for sintering foil:

[0084] (1) 78 parts of aluminum powder, 8 parts of polyvinylidene fluoride and 90 parts of dimethylformamide were mixed according to weight parts, and the aluminum alloy powder was uniformly dispersed in dimethylformamide by a first high-speed ball mill at a speed of 420 r / min for 7 hours to form a uniform aluminum powder slurry;

[0085] (2) Mix 3 parts of silicon phosphide, 1.5 parts of black phosphorus, 2.5 parts of isopropanol and 12 parts of dihydro-L-glucose ketone according to weight parts, and use a cell crusher to evenly disperse the silicon phosphide and black phosphorus in the dihydro-L-glucose ketone to obtain a dihydro-L-glucose ketone dispersion in which silicon phosphide and black phosphorus are evenly distributed;

[0086] (3) Add the silicon phosphide and black phosphorus dihydrogen levorotatory glucosone dispersion described in step (2) to the aluminum powder slurry described in step (1), and perform a second high-speed ball milling at a rotation speed of 420 r / min for 7 h to evenly disperse the silicon phosphide and black phosphorus in the slurry to obtain a slurry for sintering foil.

[0087] Comparative Example 4

[0088] Preparation of slurry for sintering foil:

[0089] (1) 78 parts of spherical aluminum alloy powder, 8 parts of polyvinylidene fluoride and 90 parts of dimethylformamide were mixed according to weight parts, and the aluminum alloy powder was uniformly dispersed in dimethylformamide by a first high-speed ball mill at a speed of 420 r / min for 7 hours to form a uniform aluminum alloy powder slurry;

[0090] (2) Mix 3 parts of silicon phosphide, 1.5 parts of black phosphorus and 12 parts of dimethylformamide according to weight parts, and use a cell crusher to evenly disperse the silicon phosphide and black phosphorus in dimethylformamide to obtain a dimethylformamide dispersion of silicon phosphide and black phosphorus evenly distributed;

[0091] (3) adding the dimethylformamide dispersion of silicon phosphide and black phosphorus described in step (2) to the aluminum alloy powder slurry described in step (1), and performing a second high-speed ball milling at a rotation speed of 420 r / min for 7 h to uniformly disperse the silicon phosphide and black phosphorus in the slurry to obtain a sintered foil slurry;

[0092] The preparation method of the spherical aluminum alloy powder is as follows: 70 parts of aluminum powder, 4 parts of silicon carbide, 13 parts of nano zinc powder, 2.5 parts of magnesium powder, and 2.5 parts of titanium powder are mixed according to weight parts, and the temperature is maintained at 750°C for electromagnetic induction heating to gradually melt into a metal liquid; then, under the action of nitrogen injection at a pressure of 200 kPa and a speed of 700 m / s, the metal liquid is blown into micron-sized droplets, and cooled into a spherical aluminum alloy powder with an average particle size of 2-3 μm;

[0093] The surface of silicon carbide is plated with a tin-lead alloy layer; the average particle size of silicon carbide is 1-2 μm.

[0094] Experimental example

[0095] The sintered foil slurries prepared in Examples 1-4 and Comparative Examples 1-4 were taken to observe whether the powders were evenly dispersed.

[0096] The sintered foil slurries prepared in Examples 1-4 and Comparative Examples 1-4 were applied to the surface of an aluminum foil substrate, respectively, and sintered at 500° C. to form sintered foils, and their compressive strength, porosity, stability and specific capacity were tested.

[0097] The compressive strength is tested according to the standard of GB / T 4740-1999.

[0098] Stability test: through 20℃-1200℃ cycle 10 times thermal shock test, calculate the powder removal rate per unit area.

[0099] The test data is shown in Table 1 below:

[0100] Table 1

[0101]

[0102] It can be seen from Table 1 that the powder of the slurry for sintered foil prepared in Examples 1-4 of the present application is evenly dispersed, and the prepared sintered foil has high compressive strength, high porosity, high specific capacity and strong stability.

[0103] The preparation raw materials of Comparative Example 1 do not contain silicon phosphide, and the rest are the same as Example 1. The porosity and specific capacity of the sintered foil prepared in Comparative Example 1 by sintering the slurry are significantly reduced, and the compressive strength and stability are also deteriorated, indicating that the silicon phosphide of the present application has excellent high-temperature stability, high power characteristics, high thermal conductivity and corrosion resistance. Adding it to the slurry can improve the heat dissipation, corrosion resistance and stability of the sintered foil. At the same time, it has a high specific surface area. Adding silicon phosphide during the sintering process is beneficial to the contact between aluminum alloy powders, thereby improving the sintering performance.

[0104] The preparation raw materials of Comparative Example 2 do not contain black phosphorus, and the rest are the same as Example 1. The porosity and specific capacity of the sintered foil prepared in Comparative Example 2 by sintering the slurry are significantly reduced, and the compressive strength and stability are also deteriorated, indicating that the black phosphorus of the present application has an ultra-high specific surface area as a two-dimensional material. Adding black phosphorus during the sintering process is beneficial to the contact between aluminum alloy powders, thereby improving the sintering performance and improving the comprehensive performance of the sintered foil. At the same time, black phosphorus has a high specific capacity, and adding an appropriate amount of black phosphorus can increase the specific capacity of the sintered foil. In addition, the high strength of black phosphorus can further improve the mechanical properties of the sintered foil.

[0105] In the preparation raw materials of Comparative Example 3, aluminum powder is used instead of spherical aluminum alloy powder, and the rest are the same as Example 1. The porosity and specific capacity of the sintered foil sintered by the sintered foil slurry prepared in Comparative Example 3 are significantly reduced, and the compressive strength and stability are also deteriorated, indicating that the spherical aluminum alloy powder of the present application has a large specific surface area, which helps to achieve a micro-melting state between aluminum alloy powders and between aluminum alloy powders and aluminum foil during sintering, so that they can be effectively combined to form a porous spherical stacking structure, thereby improving the specific capacity of the aluminum alloy powder sintered anode foil.

[0106] The preparation raw materials of Comparative Example 4 do not contain isopropanol, and dihydrolevoglucose ketone is replaced by an equal amount of dimethylformamide, and the rest are the same as Example 1. The sintered foil slurry powder prepared in Comparative Example 4 is agglomerated, and the stability and specific capacity of the sintered foil are significantly reduced, and the compressive strength and porosity are also deteriorated. This shows that the addition of surfactant, dimethylformamide and dihydrolevoglucose ketone in the preparation method of the present application can improve the surface activity of the powder, reduce the agglomeration of the powder, and make the particle size distribution more uniform, thereby improving the comprehensive performance of the sintered foil. The effect of the combination of dimethylformamide and dihydrolevoglucose ketone is better than that of using dimethylformamide alone, which can maintain the dispersed state of the particles and improve the stabilizing effect on the sintered foil slurry powder.

[0107] Although the embodiments of the present application have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions or variations may be made to the embodiments without departing from the principles and purpose of the present application, and that the technical solutions after these changes, modifications, substitutions or variations will fall within the scope of protection of the present application.

Claims

1. A method for preparing a sintered foil slurry, characterized in that: The following steps are involved: (1) 70-85 parts of spherical aluminum alloy powder, 5-10 parts of polyvinylidene fluoride and 80-100 parts of dimethylformamide are mixed according to weight parts, and the aluminum alloy powder is uniformly dispersed in the dimethylformamide by a first high-speed ball mill to form a uniform aluminum alloy powder slurry; (2) Mixing 2-4 parts of silicon phosphide, 1-2 parts of black phosphorus, 2-3 parts of a surfactant and 10-15 parts of dihydro-L-glucose ketone according to weight parts, and uniformly dispersing the silicon phosphide and black phosphorus in the dihydro-L-glucose ketone using a cell crusher to obtain a dihydro-L-glucose ketone dispersion in which silicon phosphide and black phosphorus are uniformly distributed; (3) adding the silicon phosphide and black phosphorus dihydrogen levorotatory glucosone dispersion liquid described in step (2) to the aluminum alloy powder slurry described in step (1), and performing a second high-speed ball milling to evenly disperse the silicon phosphide and black phosphorus in the slurry to obtain a sintered foil slurry; The spherical aluminum alloy powder in step (1) comprises the following raw materials in parts by weight: 60-80 parts of aluminum powder, 3-5 parts of silicon carbide, 10-15 parts of nano zinc powder, 2-3 parts of magnesium powder, and 2-3 parts of titanium powder; The method for preparing spherical aluminum alloy powder comprises the following steps: mixing the raw materials for preparing spherical aluminum alloy powder according to weight parts, performing electromagnetic induction heating, and gradually melting into metal liquid; then, under the action of inert gas injection, the metal liquid is blown into micron-sized droplets, and cooled into spherical aluminum alloy powder; The average particle size of the spherical aluminum alloy powder is 2-3 μm; The surface of the silicon carbide is plated with a tin-lead alloy layer.

2. The method for preparing a sintered foil slurry according to claim 1, characterized in that: The surfactant in step (2) is selected from one of ethanol, isopropanol, glycerol and citric acid.

3. The method for preparing a sintered foil slurry according to claim 1, characterized in that: The heating temperature is 700-800° C.; the pressure of the inert gas injection is 100-300 kPa; and the speed of the inert gas injection is 600-800 m / s.

4. The method for preparing a sintered foil slurry according to claim 1, characterized in that: The average particle size of the silicon carbide is 1-2 μm.

5. The method for preparing a sintered foil slurry according to claim 1, characterized in that: The rotation speed of the first high-speed ball milling in step (1) is 300-600 r / min, and / or the rotation speed of the second high-speed ball milling in step (3) is 300-600 r / min.

6. The method for preparing a sintered foil slurry according to claim 1, characterized in that: The time of the first high-speed ball milling in step (1) is 5-10 hours, and / or the time of the second high-speed ball milling in step (3) is 5-10 hours.

7. Slurry for sintered foil prepared by the method for preparing slurry for sintered foil as claimed in any one of claims 1 to 6.

8. Use of the sintered foil slurry as claimed in claim 7 in the production of sintered foil.

Citation Information

Patent Citations

  • Electrode material for aluminum electrolytic capacitor, and production method thereof

    CN105393320A

  • Bi-component aluminum paste for anode sintered foil of aluminum electrolytic capacitor and preparation method of bi-component aluminum paste

    CN113658803A